(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Tea has become one of the cheapest and most widely used beverages all around the world. India alone contributes around 1 billion kg of tea out of 4 billion kg of total world production. In India, tea is mostly produced in the North-East region accounting 3/4th of the country‟s total tea production, with Assam contributing around 52.0 % of the nation‟s total tea production and 15.6 % of world‟s total tea production. The performance of the Assam Tea Industry was quite commendable. The Tea Industry of Assam plays a very important role in the State as well as the National Economy in terms of revenue and employment and also occupies a vital position in the global economy, however, the average yield of tea per hectare in Assam has reduced from 1,680 kg in 1990 to 1593 kg per hectare in 2007 which is due to financial constraints, unskilled workers, the heavy cost of production etc. Amidst all these continued problems, there is still optimism for the future and a chance and potential for primary sector to uplift the economy of the state. In this paper, an attempt has been made to discuss the role, problems and prospects of the tea industry of Assam.